Pengaruh Model Pembelajaran Discovery Learning Terhadap Kemampuan Berpikir Kritis Siswa Pada Pembelajaran PKN Di MIN 12 Medan - Sekar Dea Lestari (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The purposes of this research are 1) to determine students' critical thinking skills without using the Discovery Learning learning model in Civics class VI MIN 12 Medan City, 2) to determine students' critical thinking skills using the Discovery Learning learning model in Civics class VI MIN 12 City Medan, 3) to determine the significant effect of the Discovery Learning learning model on students' critical thinking skills in Civics learning at MIN 12 Medan City. The research methodology uses a quantitative approach with the type of Quasy Experiment in the form of Nonequivalent Control Group Design. This research was conducted at MIN 12 Medan City, Medan Tembung District. The sample in this study consisted of 2 classes, namely the experimental class and the control class. Collecting data in this study used the results of pre-test and post-test essay questions. The data analysis techniques used are descriptive, normality test, homogeneous test and Wilcoxon test. The results of this study show 1) the results of students' critical thinking without the application of the Discovery Learning model obtain an average posttest score of 75.77. 2) The results of students' critical thinking applied to the Discovery Learning model obtained an average posttest score of 78.27. This shows that there is a significant influence on the learning model media Discovery Learning on students' critical thinking skills. This is evidenced by the results of the Wilcoxon test with an asymp.Sig value of 0.000 <0.05, which means that there is a change in the average of the two paired samples, Ho is accepted and Ha is rejected.